Information technology on employee performance with job satisfaction as a mediating variable - Kaleb Renhard; Herning Indriastuti (Priviet Social Sciences Journal, 2026)
Information Technology on Employee Performance with Job Satisfaction as a Mediating Variable in the Sangasanga District, Kutai Kartanegara Regency. Under the guidance of Mrs. Dr. Herning Indriastuti, S.E., M.M.. This study examined the effect of information technology on employee performance, with job satisfaction serving as a mediating variable, in the Sangasanga District, Kutai Kartanegara Regency. A quantitative approach was employed, and data were collected through online questionnaires distributed to employees. The sample consisted of 40 staff members working at sub-district and district offices in Sangasanga. The data were analyzed using SmartPLS 3.0. The findings revealed that information technology had a positive but not statistically significant effect on employee performance. However, information technology had a positive and significant impact on job satisfaction, and job satisfaction significantly and positively influenced employee performance. Furthermore, information technology indirectly exerted a positive and significant effect on employee performance through job satisfaction as a mediating variable.